STAR Guideline Terminology (I): Planning and Launching - LI Zhewei; SHI Qianling; LIU Hui; LUO Xufei; WANG Zijun; TIAN Jinhui; GE Long; CHEN Yaolong; Methodology and Technology Specialisation Committee of the STAR Working Group (Xiehe Yixue Zazhi)
ObjectiveTo develop a guideline terminology system and promote its standardization, thereby enhancing medical staff's accurate understanding and correct application of guidelines.MethodsA systematic search was conducted for guideline development manuals and method ological literature (as of October 25, 2024). After screening, relevant terms from the guideline planning and launching stages were extracted and standardized. The term list and definitions were finalized through discussion and evaluation at a consensus conference.ResultsA total of 36 guideline manuals and 14 method ological articles were included, and 27 core terms were identified.ConclusionsThe standardization of guideline terminology is essential for improving guideline quality, facilitating interdisciplinary communication, and enhancing other related aspects. It is recommended that efforts to advance the standardization and continuous updating of the terminology system should be prioritized in the future to support the high-quality development of guidelines.